CIVILIZATIONAL DEVELOPMENT AS A PREREQUISITE FOR PROGRESS IN ACHIEVING THE GOALS OF SUSTAINABLE DEVELOPMENT - Viktoriia Rudevska; Natalia Shvetz; Viktoria Tanase (Соціально-економічні відносини в цифровому суспільстві)
In this article, an attempt is made to explore the similarities and differences between the concepts of civilization development and sustainable development, considering various scientific and practical approaches to understanding the concept of sustainable development. A critical analysis of theoretical approaches to define the concepts of "sustainable development" and "civilizational development" revealed that dominant perspectives focus on the ecological component and balancing the needs of future generations. This analysis allowed the authors to formulate their vision, emphasizing the tri-vector structure of sustainable development and its dependence on the level of civilization development in society. Using the example of the degree of implementation of sustainable development principles across individual states, it has been demonstrated that countries and societal organizations based on the principles of civilizational order also show a higher degree of implementation of sustainable development goals. The article argues that achieving social and humanitarian goals is an integral component for both civilized societies and in the process of transitioning to the concept of sustainable development. Maintaining a focus solely on ecological or economic components cannot ensure the harmonious development of society at the level of individual states and on a planetary scale. Thus, consideration of civilizational development in the context of sustainable development opens up opportunities for a deeper and more comprehensive approach to solving modern problems of mankind.